Formation of Orthographic Representations in Spanish Dyslexic Children: The Role of Syllable Complexity and Frequency. (9th January 2017) - Suárez‐Coalla, Paz; Cuetos, Fernando
Abstract : Recent studies have suggested that Spanish children with dyslexia have difficulty storing orthographic representations of new words. But given that the syllable plays an important role in word recognition in Spanish, it is possible that the formation of orthographic representations is influenced by the characteristics of the syllables that make up the words. The objective of this study was to determine whether syllabic frequency and syllabic complexity influence orthographic learning in children with dyslexia. We compared the performance of a group of dyslexic children with that of a group of typical readers on a task that involved reading short and long pseudowords six times; we manipulated the frequency and complexity of the syllables from which the pseudowords were constructed. The results showed that dyslexic children do not benefit from syllabic simplicity or frequency when it comes to storing orthographic representations as the length effect in the dyslexic group remained was unchanged after repeated readings, regardless of stimulus characteristics. Copyright © 2017 John Wiley & Sons, Ltd.